In vitro degradation of ZnO flowered coated Zn-Mg alloys in simulated physiological conditions - Alves, Marta M; Prosek, Tomas; Santos, Catarina F; Montemor, Maria F (Materials science & engineering. C, Materials for biological applications, 2017)
Flowered coatings composed by ZnO crystals were successfully electrodeposited on Zn-Mg alloys. The distinct coatings morphologies were found to be dependent upon the solid interfaces distribution, with the smaller number of bigger flowers (ø 46μm) obtained on Zn-Mg alloy containing 1wt.% Mg (Zn-1Mg) contrasting with the higher number of smaller flowers (ø 38μm) achieved on Zn-Mg alloy with 2wt.% Mg (Zn-2Mg). To assess the in vitro behaviour of these novel resorbable materials, a detailed evaluation of the degradation behaviour, in simulated physiological conditions, was performed by electrochemical impedance spectroscopy (EIS). The opposite behaviours observed in the corrosion resistances resulted in the build-up of distinct corrosion layers. The products forming these layers, preferentially detected at the flowers, were identified and their spatial distribution disclosed by EDS and Raman spectroscopy techniques. The presence of smithsonite, simonkolleite, hydrozincite, skorpionite and hydroxyapatite were assigned to both corrosion layers. However the distinct spatial distributions depicted may impact the biocompatibility of these resorbable materials, with the bone analogue compounds (hydroxyapatite and skorpionite) depicted in-between the ZnO crystals and on the top corrosion layer of Zn-1Mg flowers clearly contrasting with the hindered layer formed at the interface of the substrate with the flowers on Zn-2Mg.
Keywords: hořčík; ZnO electrodeposition; Spectrum Analysis, Raman; Zinc; Zn-Mg alloys; koroze; Raman mapping; Corrosion; In vitro degradation; Zinc Oxide; Electroplating; Dielectric Spectroscopy; spektrometrie rentgenová emisní; impedanční spektroskopie; Magnesium; oxid zinečnatý; zinek; slitiny; Coated Materials, Biocompatible; pokovování galvanické; Alloys; Functional coatings; biokompatibilní potahované materiály; Ramanova spektroskopie; Spectrometry, X-Ray Emission